REVISITING STRATEGIC HUMAN RESOURCE BEHAVIOR AND DEVELOPMENT OF SUSTAINABLE COMPETITIVE ADVANTAGE (A CASE STUDY OF THREE SELECTED BUSINESS SECTORS IN INDONESIA) - Lukitasari, Dewi Diana (Universitas Pendidikan Indonesia (UPI), 2023)
The importance of human capital within organizations and the speed and methods of knowledge acquisition are highlighted by intense global competition and the rapidity of change. This study explores the importance of Strategic Human Resources Management (SHRM) features in the telecommunications industries, as well as their potential for establishing competitive business advantage. The research is based on a case study of three business sectors in Indonesia; each business sector is represented by one company (hereafter, it is called a, b, and c) and the cooperative ties developed by the firm in response to the increasingly dynamic and competitive environment. Following the completion of the appropriate tests and examinations, a, b, and c were found to be among those organizations that recognize the importance of human resources in organizational success. Through SHRM, these companies recognize the importance of their people in making a difference in their organizations and supplying the necessary component for their competitive advantage. Accordingly, it was evident that a good fit within the organization can lead to several positive benefits. People are more committed to their organizations, more satisfied with their jobs, and earn more than people who do not learn to fit in with their organizations. Furthermore, people who are well-socialized, trained and content with the organization they work in are less likely to quit their jobs and more likely to build successful careers within the organization. Training and human behavior procedures are regarded as a source of competitive advantage in the context of organizational and individual socialization.